Risk Management in Business Firms of Kathmandu Valley - Thagunna, Milan (Nepalese Journal of Business, 2025)
This study examines the risk management in business firms of Kathmandu valley. Non-performing loan is selected as the dependent variables. Similarly, bank size, liquidity ratio, return on assets, loan loss provision and capital adequacy ratio are selected as the independent variables. This study is based on secondary data of 20 banks with 140 observations for the study period from 2014/15 to 2020/21. The data were collected from Banking and Financial statistics published by Nepal Rastra bank and the annual reports of respective banks. The correlation coefficients and regression models are estimated to test the significance and importance of risk management in business firms of Kathmandu valley. The study revealed that bank size has a positive impact on non-performing loan. It means that increase in bank size leads to increase in non-performing loan. Likewise, liquidity ratio has a positive impact on non-performing loan. It shows that higher the liquidity ratio, higher would be the non-performing loan. In addition, return on assets has a negative impact on non-performing loan. It shows that higher the return on assets, lower would be the non performing loan. Likewise, loan loss provision has a negative impact on non-performing loan. It indicates that increase in loan loss provision leads to decrease in non-performing loan. Similarly, capital adequacy ratio has a positive impact on non-performing loan. It indicates that increase in capital adequacy ratio leads to increase in non performing loan.